Análise da orientação à cadeia de suprimentos de um terminal de containers: um modelo para gestão de diferentes níveis estratégicos de relacionamento. - Branco, Murilo Vidal (Universidade do Vale do Rio dos Sinos, 2013)
There are increasing studies focused on the development of integration strategies and guidance to the supply chain. However, the specificity of each chain requires studies delineated according to the characteristics of each industry. This work intends to present a model that assists in managing strategic relationships of a container terminal, based on concepts related to supply chain orientation. The model is derived from the extent of the integration model proposed by Lambert et al. (1998) and the measurement model of the integration of port terminals, developed by Song and Panayides (2007) and Panayides and Song (2008). At this model are defined three different levels of strategic relationships: monitoring, mediation and creating solutions developed from market intelligence and targeted to key relationships scaled by the strategy of the port terminal. This study proposes to apply the model developed in Tecon Rio Grande, container terminal at the Port of Rio Grande, from two stages of research. The first step is a quantitative research and served to scale the adhesion between the chain orientation strategies of the organization with respect to their key relationships, identifying possible discrepancies. In this first step is also presented the map of the strategic relationship orientation, a fundamental tool for analysis. The second stage it is a qualitative research conducted to identify the reasons for the distortions noted by the chain members. Empirical results demonstrate that the extended model presented can be used as a tool for management of key relationships.
Keywords: Market intelligence; Port terminal; Port management; Supply chain orientation; Supply chain management; Inteligência de mercado; Gestão de relacionamentos chave; Gestão portuária; Orientação à cadeia de suprimentos; Gestão da cadeia de suprimentos; ACCNPQ::Ciências Sociais Aplicadas::Administração